Study on performance of concrete with over-burnt bricks aggregates and micro-silica admixture. (September 2016) - Praveen, K; Sathyan, Dhanya; Mini, K M
Abstract: Concrete is made by mixing cement, sand, aggregates and water in required proportion, where aggregates occupy the major volume. Addition of aggregates in concrete improves properties of concrete. With the natural resources depleting rapidly, limiting the use of natural resources and enhancing the use of waste materials is very important for sustainable development. Over-burnt bricks are a waste material which cannot be used in construction directly because of their irregular shape and dark colour. Use of over-burnt bricks helps to preserve natural aggregate source. The present study focuses on the effects of microsilica at various percentages as a partial cement replacement in concrete with over-burnt bricks as coarse aggregates. The mechanical properties of hardened concrete such as splitting tensile strength, flexural strength and compressive strength are studied and analyzed.